Pembangunan Desa Migran Produktif (Desmigratif) dengan Pendekatan Perencanaan Secara Holistik, Temanik, Integratif, dan Spasial - Yeni Nuraeni (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2021)
The Development of Productive Migrant Villages (desmigrative) pioneered by the Ministry of Manpower isintended to provide protection for Indonesian Migrant Workers Candidates (CPMI) / Indonesian Migrant Workers (PMI) and improve the welfare of their families, by offering 4 main programs, namely migrationservices, community parenting, productive business. and desmigrtif cooperatives. The success development of desmigratif is largely determined by the coordination and collaboration between Ministries / Agencies and other government and non-government agencies.Based on the results of the evaluation of the villages that are the object of productive migrant village development, it turns out that there are still many problems faced by the village government and the village community in order to be able to implement the 4 desmigrative pillar programs.This study aims to examine the problems that occur in desmigratif development associated with the concept of budgeting and planning. His research uses secondary data and primary data obtained from survey locations in 5 villages which are the objects of desmigratif development spread across 5 provinces. Data analysis was performed using qualitative methods. The results showed that the problems that occurred were due to the not yet implemented coordination and collaboration in the implementation of desmigratif development. The Ministry of Manpower needs to approach Ministries / Institutions as well as other government and non-government agencies and formulate strategic steps to implement the money follow program budgeting paradigm and a Holistic-Thematic-Integrative - and Spatial planning approach based on the 2020 RPJMN national priority development agenda. -2024.